Study of chromosomal and nucleolar aspects in testes of Nysius californicus (Heteroptera: Lygaeidae) - Souza, H. V. [UNESP]; Bicudo, H. E M C [UNESP]; Itoyama, M. M. [UNESP] (My University, 2007)
In Nysius californicus (family Lygaeidae, subfamily Orsillinae), a pest commonly known as the seed bug, the chromosome complement is 2n = 16 (12A + 2m + XY), testes are formed by seven seminiferous tubules covered by an orange-colored membrane, and spermatogenesis is cystic. At prophase, sex chromosomes are heteropycnotic and autosomes usually show a chiasma. At metaphase, sex chromosomes along with microchromosomes may be seen located at the center of a ring formed by the remaining autosomes. A characteristic specific of N. californicus was the presence of nucleolar material observed from the cystic cell to the completely differentiated spermatozoon. Variations in size, shape and location of the nucleolar material occur during this process, denoting a variable degree of activity in the different stages. ©FUNPEC-RP.
Keywords: Heteroptera; Heteropycnosis; Karyotype; Lygaeidae; Nucleolar corpuscles; Nysius californicus; animal tissue; autosome; chromosome analysis; chromosome chiasm; chromosome NOR; controlled study; male; metaphase chromosome; microchromosome; mitosis rate; nonhuman; nucleolus; pest organism; prophase; seminiferous tubule; sex chromosome; sex determination; spermatogenesis; spermatozoon; sunflower; testis; animal; cytology; genetics; meiosis; physiology; Orsillinae; Xyonysius californicus; Animals; Male; Meiosis; Nucleolus Organizer Region; Seminiferous Tubules; Sex Chromosomes; Spermatogenesis